The Lingua Franca Core and Englishes in East and Southeast Asia - Deterding, David; Mohamad, Nur Raihan (Asiatic: IIUM Journal of English Language and Literature, 2016)
It has been argued, especially by Jenkins (2000, 2007), that it should not be the goal of learners to imitate speakers from the UK or USA. Instead, they should aim to achieve mutual intelligibility with other speakers of English as a Lingua Franca from around the world. This led her to propose the Lingua Franca Core, an inventory of pronunciation features that she suggests are necessary for maintaining intelligibility in international communication, while features outside the core are unimportant. However, the Lingua Franca Core remains controversial. This paper presents an overview of the pronunciation features of four varieties of English in the Outer Circle (using the Three Circles model of Kachru, 1985), Brunei English, Hong Kong English, Malaysian English and Singapore English, and one variety in the Expanding Circle, Chinese English, to assess the implications of the Lingua Franca Core for these varieties that have developed their own styles of pronunciation that increasingly distinguish them from Inner Circle styles of pronunciation.Â 